2020
DOI: 10.7150/thno.47118
|View full text |Cite
|
Sign up to set email alerts
|

An emerging role of regulatory T-cells in cardiovascular repair and regeneration

Abstract: Accumulating evidence has demonstrated that immune cells play an important role in the regulation of tissue repair and regeneration. After injury, danger signals released by the damaged tissue trigger the initial pro-inflammatory phase essential for removing pathogens or cellular debris that is later replaced by the anti-inflammatory phase responsible for tissue healing. On the other hand, impaired immune regulation can lead to excessive scarring and fibrosis that could be detrimental for the restoration of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…Furthermore, myeloid cell activation after neonatal HIE has been well-documented 111 , 112 . The M1 pro-inflammatory macrophage phenotype is associated with increased production of pro-inflammatory cytokines 113 - 116 , and the M2 anti-inflammatory macrophage phenotype is related to tissue repair, phagocytosis of protein aggregates, and removal of cellular debris 117 , 118 . An M1/M2 polarization has been shown to play an important role in HIE pathophysiological development 119 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, myeloid cell activation after neonatal HIE has been well-documented 111 , 112 . The M1 pro-inflammatory macrophage phenotype is associated with increased production of pro-inflammatory cytokines 113 - 116 , and the M2 anti-inflammatory macrophage phenotype is related to tissue repair, phagocytosis of protein aggregates, and removal of cellular debris 117 , 118 . An M1/M2 polarization has been shown to play an important role in HIE pathophysiological development 119 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that immune cells have different effects on macrophage polarization in immature hearts compared to adult cardiac tissue. Thus, it was generally accepted that T regs promote M2 phenotypes in an adult heart [ 98 ]. However, recently, Li and colleagues demonstrated that in neonatal hearts, T regs suppress the activation of M2 macrophages and inhibit fibrosis [ 99 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…In addition to their immunosuppressive properties, Tregs mediate tissue repair by synthesizing “pro-repair” molecules, such as AREG and keratinocyte growth factor (KGF) that directly promote tissue regeneration [ 31 , 35 , 36 ]. KGF secreted by activated Tregs promotes alveolar epithelial repair, while Treg-derived AREG, an epidermal growth factor receptor (EGFR) ligand, induces mitogenic and cell differentiation signals, enabling reparation of injured muscles, lungs and colons by promoting differentiation of tissue resident stem cells and progenitor cells [ 31 , 35 , 36 , 37 ]. Additionally, Tregs may promote tissue regeneration by inducing the proliferation of endothelial and parenchymal cells [ 38 , 39 ].…”
Section: An Interplay Between Mscs and Tregs In Tissue Repair And mentioning
confidence: 99%